Synthesis of some α,β-unsaturated ketones from 3-acetyl-4-hydroxy-N-methyl quinonlin-2-one. - Thảo, Nguyễn Minh; Thư, Vũ Thị Minh; Sơn, Trần Văn (Vietnam Journal of Chemistry, 2012)
The reaction of N-methylaniline with diethylmalonate has given 3-acetyl-4-hydroxy-N-methylquinolin-2-one, which in condensation with aromatic aldehydes has afforded new α, β-unsaturated ketones. Structure of these compounds has been confirmed by IR, 1H-NMR and MS spetroscopic data. Biological activities of α, β-unsaturated ketones have been investigated.